Proces razvoja nove varne "normalnosti" v (zobo)zdravstvu z vidika integriranega (individualnega in sistemskega) odziva na epidemijo COVID-19 - Zupančič, Vesna (Družboslovne razprave, 2021)
The COVID-19 pandemic rapidly affected every aspect of our day-to-day lives and soon also became a global challenge for healthcare systems. The key issues concern the health system's readiness for the "shock", the speed at which the outbreak of the "shock" was detected and responded to, how to cope with the "shock effect", and how to restore the system and learn. It is about what is known as system resistance. The aim of the research was to demonstrate the importance of collective and individual responsibility in the response to the pandemic "shock" in the chosen field of medicine: dentistry. A qualitative study of the case of the Slovenian healthcare system's resistance to the COVID-19 epidemic in terms of dental care in Slovenia was carried out.
Keywords: Covid-19; Dentistry; Epidemics; Epidemije; individual and collective responsibility; individualna in kolektivna odgovornost; odpornost sistema zdravstvenega varstva; resilience of the healthcare system; Socialna služba; Zobozdravstvo